Straits of Malacca and Singapore: pride of the Malay archipelago, priceless maritime heritage of the world - Mohd Hazmi Mohd Rusli, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2012)
Historical records reveal that port-kingdoms began to flourish along the Straits of Malacca and Singapore as early as the third century AD. These realms survived by regulating and exploiting trade flows between China and India and within the Malay Archipelago itself. After the fall of the Malacca Sultanate in 1511, the competition for supremacy in the Strait of Malacca continued between the regional Empires and their Western rivals until eventually, the latter were victorious. The Malay World then fell into centuries of Western colonization before the region gradually gained independence in the 20th century. Now, the Straits of Malacca is considerably bordered by Malaysia and Indonesia while the Straits of Singapore is jointly shared by Malaysia, Indonesia and Singapore. These Straits serve not only as two of the most important sea lines of communication in the world, but also are important economic lifelines for the coastal population. For centuries, these waterways have remained intact with their reputation as critical trading route and due to their remarkable significance, the Straits of Malacca and Singapore are undoubtedly priceless heritage of the maritime world.